A corpus‐based investigation of world Englishes in literature. Issue 1 (21st June 2016) - PERCILLIER, MICHAEL; PAULIN, CATHERINE
ABSTRACT: Given the spread of English as a world language and the subsequent development of numerous varieties during the colonial and postcolonial periods, the emergence of local literatures using local varieties of English was only a matter of time. The sheer diversity of new Englishes, literary traditions and motivations to use the localised features in writing results in a wide range of strategies at the disposal of writers who choose to incorporate such features in their work. By compiling a corpus of selected literary works, an analysis of various distinctive features is performed, which makes it possible to address the following questions: Which localised features of English are represented in our corpus? What is the motivation to use a particular set of localised features? Is the representation of such linguistic variation in writing a symbolic or mimetic enterprise?